Financial Literacy and Well-Being of Lampung MSMEs: Evidence from Islamic Financing Access - Miswan Gumanti; Eka Pariyanti (Jurnal Economia, 2026)
This study examines how Islamic financial attitude, knowledge, awareness, and financial confidence influence the financial well-being of Micro, Small, and Medium Enterprises (MSMEs) owners, while assessing the moderating role of access to Islamic financing. A quantitative survey of 308 MSME owners in Lampung Province, Indonesia, was analyzed using JASP to test direct and moderation effects. Findings reveal that Islamic financial attitude, knowledge, awareness, and financial confidence significantly enhance MSME owners’ financial well-being. Access to Islamic financing further strengthens these relationships, highlighting its role in maximizing the benefits of Islamic financial engagement. Guided by the Theory of Planned Behavior, the study identifies key cognitive and behavioral determinants of financial well-being within the Islamic finance context and addresses a gap in the literature. Practical implications emphasize fostering positive financial attitudes, improving knowledge and awareness, strengthening financial confidence, and expanding access to Islamic financing to support sustainable MSME financial well-being.